Valorization of biomass-derived magnetic activated carbon from vinasse and grape marc for sustainable bitumen modification - Ozdemir, Ahmet Munir; Yilmaz, Bahadir; Arslanoglu, Hasan (Pergamon-Elsevier Science Ltd, 2025)
Agricultural and food-processing residues represent abundant biomass resources with untapped potential for sustainable material production in the bioenergy sector. Functional renewable materials are obtained by using such residues in high-value applications such as bitumen modification. This study investigates the use of magnetic activated carbon (MAC), synthesized from by-products from bioethanol production (vinasse and grape marc) as a sustainable additive for modifying 160/220 penetration-grade bitumen. The objective is to enhance the rheological performance of bitumen under varying thermal and loading conditions. Modified binders containing 5 %, 10 %, and 15 % MAC were evaluated using dynamic mechanical analysis. Master curves for complex modulus and viscosity were developed using the Christensen-Anderson, Cross, and Carreau-Yasuda models. The results show that MAC incorporation improves elasticity, increases zero-shear viscosity, and enhances resistance to permanent deformation. In particular, it was observed that the addition of 15 % MAC increased the ZSV and G*/sin delta (64 degrees C) values by approximately 35 % and 95 % compared to pure binder, respectively. Rheological index (R) values increased by 38 %. The findings suggest that MAC-modified binders offer a promising solution for improving the performance of bituminous pavements in hot climates. Beyond advancing pavement performance, this work demonstrates a high-value utilization pathway for biomass residues, linking waste valorization to renewable material development within the bioenergy framework.
Keywords: Modified bitumen; Rheology; Cross; Carreau-Yasuda; Shear rate; Magnetic activated carbon